Vancomycin Stress Response in a Sensitive and a Tolerant Strain of Streptococcus pneumoniae - Haas, Wolfgang (American Society for Microbiology, 2005)
The vancomycin stress response was studied in Streptococcus pneumoniae strains T4 (TIGR4) and Tupelo. Vancomycin affected the expression of 175 genes, including genes encoding transport functions and enzymes involved in aminosugar metabolism. The two-component systems TCS03, TCS11, and CiaRH also responded to antibiotic treatment. We hypothesize that the three regulons are an important part of the bacterium's response to vancomycin stress.